Go With The Flow. - VILLARDI, LEOPOLDO (Architectural Record, 2025)
The article discusses the Torre Unipol tower in Milan, designed by Mario Cucinella Architects. The tower features a unique design that emulates nature to save energy and enhance thermal comfort. It includes a distinctive tessellated facade, a 230-foot-tall atrium, and a vertical chasm that acts as a spatial buffer and solar chimney. The tower's design prioritizes sustainability, achieving a LEED Platinum rating, and offers open-plan workspaces with panoramic views of the cityscape.